Effect of Hydrogen (g) Mixture with Refrigerant on the Pressure of Cooling Machine Components - S Djiwo; M. Asroni; A. Nugroho; Djoko Hari Praswanto (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2021)
Refrigerant is substance or chemical composition which alternately compressed and condensed into a liquid and then expanded into vapor or gas when pumped through the cooling system. Alternative refrigerants are needed to replace full the halogenated refrigerants which are believed to contribute to ozone depletion in the atmosphere. In the last decade, many research and development of studies on the synthesis and characterization alternative refrigerants have been carried out. With replace a limited Ozone Depleting Substance (ODS) with any alternative can involve major changes in the design of various components such as insulation, lubricants, heat exchangers and motors. The purpose of this research is to determine the effect of hydrogen mixture with refrigerant R134a on the pressure of each component. This research used an experimental method on a direct cooling device. The data which obtained from the experimental results on this cooling machine then will process to determine the pressure that occurs in each component of the cooling machine. Based on the results of this research, the effect of the hydrogen mixture on refrigerant R134a on the performance of the cooling machine is the differences density of each mixture ratio. If more of hydrogen additions there, the density of result mixture also getting smaller. This will affect the pressure that occurs in the compressor because the relationship between density and pressure is directly proportional. The conclusion is the refrigerant from a mixture of hydrogen gas and Freon R134a is suitable for use as a refrigerant for air condition. Because at 60 minutes, the mixture ratio of 85%:15% can reduce the water temperature slowly until 20.2ºC. The slow cooling is felt bad when applied on the food preservation.